Réponse :
bonjour,
A = ( x + 2 ) ( 3x - 1 ) + x² -4
A = ( x + 2 ) ( 3x - 1 ) + x² - 2²
A = ( x + 2 ) ( 3x - 1 ) + ( x -2 ) ( x + 2 )
A = ( x + 2 ) [( 3x - 1 ) + ( x - 2 )
A = ( x + 2 ) ( 3x - 1 + x-2 )
A = ( x + 2 ) ( 4x - 3 )
B = ( x + 4 ) ( 2x - 1 ) + x² - 16
B = ( x + 4 ) ( 2x - 1 ) + x² - 4²
B = ( x + 4 ) ( 2x - 1 ) + ( x-4 ) ( x + 4 )
B = ( x + 4 ) ( 2x - 1 + x - 4 )
B = ( x + 4 ) ( 3x - 5 )
C = (x - 3 ) ( x + 1 ) - (x² - 9 )
C=(x - 3 ) ( x + 1 ) - ( x² - 3² )
C = (x - 3 ) ( x + 1 ) - ( x + 3 ) ( x - 3 )
C = ( x- 3 ) ( x + 1 - ( x + 3 ) )
C = (x - 3 ) ( x + 1 - x - 3 )
C = ( x - 3 ) × -2
C = -2( x - 3 )
D = ( 2x + 1 ) ( x - 2) - ( x² - 4 )
D = ( 2x + 1 ) ( x - 2) - ( x² - 2²
D = ( 2x + 1 ) ( x - 2) - ( x -2 ) ( x + 2 )
D = ( x - 2 ) ( 2x + 1 - ( x + 2 )
D = ( x - 2 ) ( 2x + 1 - x - 2 )
D = ( x - 2 ) ( x - 1 )
E = 25 - x² - ( x - 5 ) ( 2x + 3 )
E = 5² - x² - ( x - 5 ) ( 2x + 3 )
E= (5 - x) ( 5 + x ) - ( x - 5 ) ( 2x + 3 )
E = ( 5 - x ) ( 5 + x ) + ( - x + 5 ) ( 2x + 3 )
E = ( 5 - x ) ( 5 + x ) + ( 5 - x ) ( 2x + 3 )
E = ( 5 - x ) ( 5 + x + 2x + 3 )
E = ( 5 - x ) ( 3x + 8 )
voila :)